Higroscopic behavior of Araçá-boi (Eugenia Stipitata) powder obtained by the lyophilization method with different maltodextrin concentrations (Research, Society and Development, 2021)
This study aimed to evaluate the physicochemical characteristics of freeze-dried Araçá-boi powder, and its hygroscopic behavior using adsorption isotherms and different mathematical models. The Araçá-boi pulp formulations with different concentrations of maltodextrin (14, 21 and 28%) were frozen in a freezer at -18 ° C, then dehydrated in a bench-top freeze dryer. The parameters of water content, total solids, pH and titratable acidity were determined. The water adsorption isotherms of Araçá-boi powder at temperatures of 25, 30 and 35 °C were determined using the special indirect static method, using the Aqualab hygrometer, to measure water activity. The Henderson, Oswin, Halsey, GAB and Peleg models were fitted to the water adsorption isotherms using nonlinear regression. From the coefficient of determination (R2) and the mean percentage deviation (P), it was found that, among the models studied and considering the temperatures tested, the R2 values ​​obtained in GAB, Halsey and Peleg are so close to each other that , in the worst case, they do not exceed a 0.9% difference. The best mathematical representation of the isotherms was obtained by the GAB model, since it presented the lowest values ​​for Xm, being, therefore, the model that best explains the water gain.